Performance of two updated blood glucose monitoring systems: an evaluation following ISO 15197:2013. (3rd May 2016) - Pleus, Stefan; Baumstark, Annette; Rittmeyer, Delia; Jendrike, Nina; Haug, Cornelia; Freckmann, Guido
Abstract: Objective For patients with diabetes, regular self-monitoring of blood glucose (SMBG) is essential to ensure adequate glycemic control. Therefore, accurate and reliable blood glucose measurements with SMBG systems are necessary. The international standard ISO 15197 describes requirements for SMBG systems, such as limits within which 95% of glucose results have to fall to reach acceptable system accuracy. The 2013 version of this standard sets higher demands, especially regarding system accuracy, than the currently still valid edition. ISO 15197 can be applied by manufacturers to receive a CE mark for their system. Research design and methods This study was an accuracy evaluation following ISO 15197:2013 section 6.3 of two recently updated SMBG systems (Contour* and Contour TS; Bayer Consumer Care AG, Basel, Switzerland) with an improved algorithm to investigate whether the systems fulfill the requirements of the new standard. For this purpose, capillary blood samples of approximately 100 participants were measured with three test strip lots of both systems and deviations from glucose values obtained with a hexokinase-based comparison method (Cobas Integra† 400 plus; Roche Instrument Center, Rotkreuz, Switzerland) were determined. Percentages of values within the acceptance criteria of ISO 15197:2013 were calculated. This study was registered at clinicaltrials.gov (NCT02358408). Main outcome Both updated systems fulfilled the system accuracy requirements of ISO 15197:2013 as 98.5% to 100% of the results were within the stipulated limits. Furthermore, all results were within the clinically non-critical zones A and B of the consensus error grid for type 1 diabetes. Conclusions The technical improvement of the systems ensured compliance with ISO 15197 in the hands of healthcare professionals even in its more stringent 2013 version. Alternative presentation of system accuracy results in radar plots provides additional information with certain advantages. In addition, the surveillance error grid offers a modern tool to assess a system's clinical performance.